Effects of Viscosity Index Improver on Morphology and Graphitization Degree of Diesel Particulate Matter. (May 2017) - Wang, Yajun; Liang, Xingyu; Wang, Yuesen; Yu, Hanzhengnan
Abstract: Effects of viscosity index improver on morphology and graphitization degree of diesel particulate matter were investigated. Three lubricating oils with different viscosity were tested and compared in a two cylinder, four stroke, direct injection diesel engine. 5.0 wt. % and 10 wt. % viscosity index improver were added into lubricating oil to improve the viscosity-temperature performance respectively. Transmission Electron Microscope and Raman spectroscopy were employed to analyze the primary particle size distribution and graphitization degree of diesel particles from different lubricating oils. The primary particles size distribution conformed to Gaussian distribution. When the higher viscosity lubricating oil was used, the primary particle boundaries tend to be clearer and the mean diameter is smaller at 1600 rpm and 2200 rpm. As to the graphitization degree, the ratio of the D1 band to G band areas (AD1 /AG ) increased with the increasing viscosity at 1600 rpm and 2200 rpm, indicating that the graphitization degree was lower when the higher viscosity lubricating oil was used.